Project-Based Learning: Enhancing Efl Students’ Speaking Ability Through Vlog At SMK Negeri 1 Palopo - Ni Ketut Dian Meiva Pratiwi; Reski Yusrini Islamiah Yunus; Andi Mangnguntungi Sudirman (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
The aims of this research is to find out the effectiveness of project-based learning in improving students' speaking ability through vlog at SMK Negeri 1 Palopo. The population of this research is all tenth class, with total 620 students. The sample was used is random sampling technique, with total 22 students. The method was used is quantitative method. The research design used is pre-experimental. The result of this research is the main score of the pretest is 61,00 and posttest is 76,18. Standard deviation in a pretest is 9,875 and posttest is 10, 455. This research used test of normality to measure students score. The value test of normality is 0, 039 means that data not distributed normal. So the researcher used non-parametric test, is wilcoxon test. The result is Asymp. Sig. (2-tailed) Values is 0,000. Where the value of 0, 000 < 0, 05, which mean, H1 is accepted and H0 is rejected. So, there is a difference in the average value of learning outcomes from both pretest and posttest of students. This results show that PJBL via vlog can overcome students difficulty performance and make students enthusiastic in learning speaking. So it can be concluded that using project-based learning via vlog can enhance students' speaking ability at SMK Negeri 1 Palopo.